Primary and secondary copper minerals from Rędziny, Rudawy Janowickie, Sudeten, Southwestern Poland - Orligóra, Wojciech; Gołębiowska, Bożena (Wydawnictwa AGH, 2012)
Dolomite quarry in Rędziny is a place, which has a very rich polymetallic mineralization. It is a result of hydrothermal processes (precipitated primary minerals) or chemical weathering changes (precipitated secondary minerals). Proximity to Karkonosze Granite massif greatly influenced the variety of the mineralization in Rędziny. Compared to numerous exploited mines located in the vicinity (for example Miedzianka, Ciechanowice, Czarnów, Radomierz), the dolostone quarry is relatively young, opencast mine. Sulfides are the most common primary minerals in Rędziny. This information appears in the study of Gołębiowska et al. (e.g. 1998, 2006, 2012).
Geology, Geophysics & Environment
Keywords: polymetallic mineralization; dolomite quarry; Karkonosze.